Evolved Aliphatic Halogenases Enable Regiocomplementary C−H Functionalization of a Pharmaceutically Relevant Compound. Issue 51 (18th November 2019) - Hayashi, Takahiro; Ligibel, Mathieu; Sager, Emine; Voss, Moritz; Hunziker, Jürg; Schroer, Kirsten; Snajdrova, Radka; Buller, Rebecca
Abstract: Non‐heme iron halogenases are synthetically valuable biocatalysts that are capable of halogenating unactivated sp 3 ‐hybridized carbon centers with high stereo‐ and regioselectivity. The reported substrate scope of these enzymes, however, is limited primarily to the natural substrates and their analogues. We engineered the halogenase WelO5* for chlorination of a martinelline‐derived fragment. Using structure‐guided evolution, a halogenase variant with a more than 290‐fold higher total turnover number and a 400‐fold higher apparent k cat compared to the wildtype enzyme was generated. Moreover, we identified key positions in the active site that allow direction of the halogen to different positions in the target substrate. This is the first example of enzyme engineering to expand the substrate scope of a non‐heme iron halogenase beyond the native indole‐alkaloid‐type substrates. The highly evolvable nature of WelO5* underscores the usefulness of this enzyme family for late‐stage halogenation. Abstract : Beyond natural : A protein catalyst was engineered to perform selective halogenation of a fragment of martinelline, a pharmaceutically relevant non‐native substrate. Directed evolution of non‐heme iron halogenase WelO5* afforded a variant with an up to 400‐fold higher apparent k cat and a 290‐fold higher TTN for this target substrate than the wildtype enzyme while achieving high stereo‐ and regioselectivity (>99 %).